Loneliness in the Elderly: A Qualitative Study of Loneliness Factors in the Elderly - Munawaroh, Ma’rifatul; Felasuf, Zuyyin Choiriyyatun (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to explore the experience of loneliness among older adults and the factors that influence it. Employing a qualitative approach with a phenomenological method, data were collected through in-depth interviews with two elderly individuals living in non-institutional settings. The findings reveal that loneliness in older adults is influenced by the loss of a spouse, physical distance from family, lack of meaningful social relationships, changes in the living environment, and limited emotional support. Participants who had access to social support and engaged in meaningful activities were better able to cope with loneliness compared to those who did not. The study concludes that loneliness is a subjective experience shaped by the individual’s life context. It underscores the importance of social and emotional interventions to support the psychological well-being of older adults. This study provides nuanced insights into the lived experiences of loneliness among non-institutionalized older adults in an Indonesian context, highlighting the role of social and emotional support in mitigating loneliness. It contributes to the development of culturally sensitive strategies for promoting mental health in aging populations.